Trend of De La Salle Lipa Education Graduates’ Performance in the Licensure Examination for Teachers (LET) from 2011 to 2015 - Maria Theresa Bolo Kalaw (International Journal of Evaluation and Research in Education (IJERE), 2017)
This study aimed to examine the trend of performance of De La Salle Lipa (DLSL) education graduates in the Licensure Examination for Teachers (LET). Quantitative trend analysis employed on the data collected from records officially released by the Professional Regulation Commission (PRC) for the years 2011 to 2015 revealed that the performance of both elementary and secondary education passers were significantly higher than the national passing rates and showed a significant relationship between the graduates’ English proficiency and their LET- General Education performance. When grouped according to their profile, there were significant differences in the education graduates’ performance in terms of the year LET was taken, their GPA, and results of English Proficiency and Culture Fair Intelligence Tests but not in terms of their field of specialization. These results were considered in proposing a syllabus incorporating the strategies to further improve the program offerings of the Education Department particularly in terms of curriculum development, recruitment and selection of qualified students, continuous professional training for faculty, and more intensified LET review for the education graduates. Findings of the study showed that DLSL is eligible to qualify as a Center of Development in Teacher Education in the area of instructional quality.